Islamic Microfinance as a Food Security Solution to Realize the Goal of Zero Hunger in Indonesia - Muhammad Gesit Widayatno; Wahyu Akbar; Zulkifli; Hanief Monady; Muhaimin; Muhammad Sirajuddin Qahtan Hamdan (el-Jizya: Jurnal Ekonomi Islam, 2026)
The problem of hunger remains a challenge in Indonesia, influenced by rising prices of necessities, dependence on food imports, and poor access to quality food for people experiencing poverty. In this context, Islamic Microfinance offers a relevant approach to support food security in line with the Zero Hunger goal of the SDGs. As the country with the largest Muslim population, Indonesia has an excellent opportunity to optimize sharia principles in microfinance services. Islamic Microfinance provides fair, transparent, riba-free, and inclusive financing for small farmers and micro-entrepreneurs in the food sector. This study aims to analyze the contribution of Islamic Microfinance to food security through a literature review using secondary data from relevant journals, books, and documents. The method used is a descriptive, qualitative approach with content analysis techniques. The results of the study show that institutions such as BMT play an essential role in providing sharia financing through Murabahah, Qard al-Hasan, and Mudharabah contracts, which effectively increase access to capital and enhance business sustainability. These findings confirm that Islamic Microfinance is an instrument of empowerment and a strategy to strengthen food security, thereby requiring synergy among the government, sharia financial institutions, and the community.